1998
DOI: 10.1002/hep.510270404
|View full text |Cite
|
Sign up to set email alerts
|

Independent and combined action of hepatitis C virus infection and alcohol consumption on the risk of symptomatic liver cirrhosis

Abstract: Although alcohol intake and hepatitis C virus (HCV) infection are the major determinants of liver cirrhosis (LC) in Western countries, the joint effect of these two factors on LC risk has not yet been adequately studied. We used data from two hospital-based case-control studies performed in Italy. Cases were 285 cirrhotic patients admitted for the first time to district hospitals for liver decompensation. Controls were 417 patients admitted during the same period, and in the same hospitals as the cases, for ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
52
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 302 publications
(54 citation statements)
references
References 66 publications
2
52
0
Order By: Relevance
“…Similar to other studies evaluating the factors associated with severe fibrosis, we found that duration of moderate to heavy alcohol use was an independent predictor of moderate to severe fibrosis (2,21,28,29). Definitions of "heavy" alcohol use vary across different studies and not all studies use gender-specific cut-offs.…”
Section: Discussionsupporting
confidence: 84%
“…Similar to other studies evaluating the factors associated with severe fibrosis, we found that duration of moderate to heavy alcohol use was an independent predictor of moderate to severe fibrosis (2,21,28,29). Definitions of "heavy" alcohol use vary across different studies and not all studies use gender-specific cut-offs.…”
Section: Discussionsupporting
confidence: 84%
“…There is solid evidence that excessive alcohol intake is a risk factor for the progression of liver disease caused by HCV. 17,18 The current study data appear to support that view.…”
Section: Discussionsupporting
confidence: 72%
“…Other case-control studies carried out in South Europe have demonstrated a dose-effect relationship of increased risk for both cirrhosis and HCC with increasing alcohol intake, when also adjusting for HBV and HCV infection (Corrao et al, 1993(Corrao et al, , 1997Bellentani et al, 1994;Corrao and Arico`, 1998;Kuper et al, 2000a). On the same line, two meta-analyses conducted by Corrao et al (1998aCorrao et al ( , 2004 on the risk of cirrhosis and of various neoplasms, including liver cancer, show a continuous curve of increasing risk of disease with increasing alcohol intake.…”
Section: Dose-effect Relationship and Threshold Of Safe Intakementioning
confidence: 85%
“…Some Italian studies on the aetiology of cirrhosis confirm the hypothesis of a synergism between alcohol intake and HCV or HBV infection (Corrao and Arico`, 1998). In agreement with these findings, in a French study among subjects with HCV infection, age at infection and duration of infection were associated linearly with fibrosis stage, both associations being modified by alcohol intake: patients who consumed 50 g/day or more of alcohol had a higher fibrosis Table 4 Interaction between HBV or HCV infection and heavy alcohol intake (>60 g/day of ethanol for at least 10 years) in the Brescia HCC case-control study (Donato et al, 2002, data Figure 2 Odds ratio for HCC according to alcohol intake and the presence of HBV or HCV, obtained by fitting spline regression models that included age and residence as covariates, hepatitis B surface antigen and HCV RNA in the Brescia HCC study.…”
Section: Interaction With Hepatitis C Virusmentioning
confidence: 93%